A comprehensive review of hexanol and its blends in diesel engines - Celebi, Yahya; Cengiz, Mazlum; Aydin, Ahmet; Aydin, Hueseyin (Pergamon-Elsevier Science Ltd, 2024)
Growing concerns regarding global warming, climate change, air pollutants and rising energy demand, have triggered many researchers to explore better, alternate renewable energy resources. Hexanol, a next generation fuel, which can be derived from renewable resources, has emerged as a promising candidate due to its higher energy density, greater calorific value, higher cetane number, lower latent heat of evaporation, lower hygroscopic, and lower corrosiveness when compared to the light alcohols such as methanol, and ethanol. Furthermore, it has higher flash point, and low volatility, making it safe for storage and transportation. This study provides an in-depth analysis of research on hexanol usage in diesel engines. First, the feedstocks, production methods, environmental and human health impacts, supply and demand, and the fuel application of hexanol are reported. Subsequently, different hexanol variations including single, binary blends (hexanol-biodiesel and hexanol-diesel), ternary blends (hexanol, biodiesel and petroleum diesel) and multi-blends applications are separately reviewed and compared to petrol diesel. Hence, this study clearly demonstrates the effects of hexanol on the combustion parameters, performance, and exhaust emissions of diesel engines. Consequently, it highlights general conclusions and future proposed research directions. The utilization of hexanol as a drop-in fuel has been thoroughly summarized to guide and inform future research efforts.
Keywords: Hexanol; Diesel engines; Biomass; Biodiesel; Combustion; Performance; Emission